Transparent Minds in Science Fiction An Introduction to Alien, AI and Post-Human Consciousness - Matthews, Paul (Open Book Publishers, 2023)
Transparent Minds explores the intersection between neuroscience and science fiction stories. Paul Matthews expertly analyses the narratives of humans and nonhumans from Mary Shelley to Kazuo Ishiguro across 200 years of the genre. In doing so he gives lucid insight into the meaning of existence and self-awareness. Rigorously researched and highly accessible, Matthews argues that psycho-emotional science fiction writers both imitate and inform alien and post-human consciousnesses through exploratory narratives and metaphor. Drawing from a diverse range of scholars and critics, Matthews explores topics such as psychonarration and neuroaesthetics, to create a thoughtful and cogent argument. By synthesising concepts from philosophy, neuroscience, and literary theory, Matthews posits the potential for science fiction to bridge the gap in understanding between AI and human minds. Given the recent advancements in AI technology, Matthews' timely discussion enters the speculative realm of sentient technology and postcyborg ethics. The work constitutes a major contribution to cross-disciplinary perspectives on alien and posthuman psychology, that engages with future states of existence in both ourselves and the machines we create. Transparent Minds will be of interest to innovators, authors, and science fiction enthusiasts alike.